NAVIGATING ENGLISH READING COMPREHENSION: THE ROLE OF STUDENTS' SELF-REGULATION - Ningsih, Wirda; Zalisman, Zalisman (Universitas Tribhuwana Tunggadewi, 2024)
This study aims to explore the role of student self-regulation in understanding English reading at Danul Hikmah Pekanbaru MTS. Using a quantitative research design with a correlational descriptive approach, the study involved 46 students selected through stratified random sampling techniques out of a total population of 143 students. The research instruments included a questionnaire to measure self-regulation and standard tests to measured reading understanding. The data collection process begins with validity and reliability testing of instruments through pretests, followed by primary data collection. The data analysis was performed using SPSS version 25, using descriptive statistics to summarize data and Pearson correlations to test the relationship between self-regulation and reading understanding. The results of the analysis showed a significant positive correlation between student self-regulation and their English reading understanding score. The Pearson Correlation Coefficient of 0.849 indicates a strong relationship, where a higher level of self-Regulation is associated with a better understanding of reading. These results emphasize the importance of developing self-regulation skills in students to improve their academic performance in reading. Therefore, teaching strategies that facilitate the development of self-regulation can make a positive contribution to learning outcomes. These findings recommend the application of educational interventions that focus on the development of self-regulation to improve student reading understanding and, ultimately, their overall academic performance.